Disengagement from political violence and deradicalisation: A narrative-dialogical perspective - Silva, Raquel da (2020)
This article applies a dialogical analysis to the change processes involved in moving from engagement with to disengagement from an armed militant group, as well as from radicalisation to deradicalisation. The findings underline the interplay between different push and pull factors at individual, organisational and societal levels which played a role in the already mentioned processes in three periods of time – engagement with, life within and disengagement from an armed organisation. The dialogical framework conceptualises the development trajectory as relationships between a variety of positions of the self (I-positions), which generate different personal meanings involved in processes of disengagement and deradicalisation